The Effect of Liquidity and Profitability on The Level of Financial Distress Using the Altman Z-Score Model : Study Of Companies in The Automotive Sector and Components Listed on The Indonesia Stock Exchange for the 2015-2020 Period - Nina Karlina; Robbi Saepul Rahman (LPPM STMIK Mardira Indonesia, 2023)
This research aimed to examine the impact of the current ratio and return on assets on the degree of financial distress in the automotive and component manufacturing sectors of the Indonesia Stock Exchange during the period of 2015–2020, utilizing the Altman Z-score model. Furthermore, the objective of this investigation is to examine the primary determinant between the current ratio and return on assets about the degree of financial distress, utilizing the Altman z-score model, within the automotive and component sub-sector manufacturing firms that are publicly traded in the Indonesia Stock Exchange from 2015 to 2020. The present study employs a descriptive-verification research methodology. The present study employs secondary data from information sourced from https://idx.bei.co.id/. Conduct data collection methodologies utilizing documentation techniques. The present study has selected a population of 13 manufacturing companies in the automotive and component sub-sectors listed on the Indonesia Stock Exchange from 2015 to 2020. Non-Probability Sampling was utilized to determine the sample size of ten companies that meet the established criteria. The data underwent analysis through the utilization of multiple linear regression as well as hypothesis testing via the t-test and F-test. The findings of the present investigation suggest that the current ratio and the return on assets exhibit a noteworthy and favorable impact on the degree of financial distress, as measured by the Altman z-score, at a rate of 73.4%.